Hormetic response to B-type procyanidin ingestion involves stress-related neuromodulation via the gut-brain axis: Preclinical and clinical observations - Osakabe, Naomi; Fushimi, Taiki; Fujii, Yasuyuki (Frontiers in Nutrition, 2022)
B-type procyanidins, a series of catechin oligomers, are among the most ingested polyphenols in the human diet. Results of meta-analyses have suggested that intake of B-type procyanidins reduces cardiovascular disease risk. Another recent focus has been on the effects of B-type procyanidins on central nervous system (CNS) function. Although long-term B-type procyanidin ingestion is linked to health benefits, a single oral intake has been reported to cause physiological alterations in circulation, metabolism, and the CNS. Comprehensive analyses of previous reports indicate an optimal mid-range dose for the hemodynamic effects of B-type procyanidins, with null responses at lower or higher doses, suggesting hormesis. Indeed, polyphenols, including B-type procyanidins, elicit hormetic responses in vitro, but animal and clinical studies are limited. Hormesis of hemodynamic and metabolic responses to B-type procyanidins was recently confirmed in animal studies, however, and our work has linked these effects to the CNS. Here, we evaluate the hormetic response elicited by B-type procyanidins, recontextualizing the results of intervention trials. In addition, we discuss the possibility that this hormetic response to B-type procyanidins arises via CNS neurotransmitter receptors. We have verified the direction of future research for B-type procyanidins in this review.